A legal study on termination of foetus with severe medical anomaly / Nurdiyanah Rosly … [et al.] - Rosly, Nurdiyanah; Hisham, Nor Anis; Mohd Fuad, Nursalehah; Adam, Rabiatuadawiyah (Faculty of Law, 2014)
The main purpose of this research is to propose an exception under Section 312 of Penal Code to terminate foetus that has been pre-natally diagnosed with severe medical anomaly. This issue is vital in current situation as it has taken a massive place in our society in the sense that; statistics have shown there is a tremendous increase as to the number of foetus or baby born with medical anomaly. Our research then concerns with the central dilemma whether a woman has the right to terminate her pregnancy, when it comes to her medically diagnosed foetus with anomaly. Throughout this research, we will analyse the legal, social and religious perspectives regarding this matter. From the findings, the legal view in Malaysia shows that it is not legalised under the Penal Code. Therefore, comparisons are made with the statutes in the United Kingdom which are far more advanced than us, so as to find a way to fill in the lacunae that we have in our law. Besides that, in terms of social perspectives, we have laid down several reasons as to why this issue should be legalised so as to enable the incorporation of an exception to Section 312. In addition, in terms of religions wise, generally the four main religions in Malaysia prohibit abortion but in certain situations, it is permitted. Hopefully from this research, the findings are sufficient to formulate a ground to propose incorporation of an exception under Section 312 so that we are not left far behind in terms of development of law and at the same time we could also fill in the gap in our law. It is our biggest hope that this research is beneficial to all regardless of whether they are from legal, medical, teaching field or even a layman especially the mothers.